Functional Vocabulary Measurement - Pratomo, Hafidz Triantoro Aji; Siswanto, Arif; Purnaningrum, Windiarti Dwi (Poltekkes Kemenkes Surakarta, 2023)
Background: Vocabulary is an essential component in child and individual communication performance. This ability is an indicator of language problems or disorders that may be experienced. Measuring receptive and expressive vocabulary areas is necessary to value the children’s abilities comprehensively. The provision of a vocabulary problem-examining instrument is a condition needing immediate investigation. This research aims to evaluate the validity and reliability of the Functional Vocabulary Ability Measurement instrument. Methods: This study was quantitative research. Forty (40) respondents were involved in this research with varying language problem backgrounds. The instrument trial involved clinicians with speech therapist and non-therapist backgrounds. The test-retest method was used to analyze the reliability of the instrument. Results: The result of the validity test shows a rho value for receptive and expressive vocabulary subtests with a total value > 0.800 at a significance level ≤ 0.001. The reliability value of Cronbach’s alpha test result is 0.980 for receptive vocabulary and 0.986 for expressive vocabulary components, for a total value of 0.991. The relation of the test-retest result indicates that the value of relation in the first and second measurements is 0.93 for receptive vocabulary, 0.945 for expressive vocabulary components, and a total value of 0.936. Conclusion: This research instrument has qualified validity and reliability values. Clinicians can use this instrument as one option in the child's vocabulary ability assessment process. Further research is necessary to see the impact of the instrument more broadly.